Impact of abusive leader behavior on employee job insecurity: A mediating roles of emotional exhaustion and abusive peer behavior - Li, Miao; Ahmed, Ammar; Syed, Obed Rashdi; Khalid, Nadeem; Muñoz, José E. (Frontiers in Psychology, 2022)
Based on the social exchange theory, the present study aimed to investigate the association between abusive leader behavior and job insecurity while considering the serial intervention of abusive peer behavior and emotional exhaustion. Abusive leader behavior triggers abusive peer behaviors, emotional exhaustion, and job insecurity. Results from the data of 323 final responses indicated support for all the hypothesized relationships. Moreover, the findings also reported sequential mediation of abusive peer behavior and emotional exhaustion in the association between abusive leader behavior and job insecurity. The results indicate that mistreatment by an immediate boss can encourage peers to engage in similar unethical behaviors, leading to employees feeling emotionally exhausted, which ultimately results in job insecurity concerns. The study hopes that the findings will help practitioners dedicate more efforts to curtailing abusive behaviors that lead to several unintended consequences at work.